(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Relevance: The study of the effect of vitamin D deficiency on the human body is attracting increasing attention from scientists. According to numerous studies, vitamin D deficiency is registered in half of the world’s population; among older people this figure reaches 80–90%. At the same time, vitamin D deficiency in men is most often detected in obesity, androgen deficiency, infertility and prostate diseases.